SPECIFIC FEATURES OF ENVIRONMENTAL RISK MANAGEMENT IN ENVIRONMENTAL PROJECTS - Nadia FROLENKOVA; Anatoliy ROKOCHINSKIY; Yury MAZHAYSKIY; Liubov VOLK; Natalіa PRYKHODKO; Ruslan TYKHENKO; Ivan OPENKO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The selection and justification of the feasibility of any environmental, including water projects, are always associated with the analysis of future events and uncertainty of the outcome of the project. Therefore, one of the most important tools of project management is a risk management framework. Risks usually arise from the uncertainty and variability of the economic, environmental, political, social environment, as well as the different operation conditions of a particular object. Weather and climate risk, as a subtype of general environmental risk, reflects the degree of loss of potential yields, and consequently the amount of income, as a result of uncontrolled meteorological factors. Reducing such risk provides a decrease in the impact of adverse natural factors on the efficiency of economic activity, and hence on the degree of technological excellence and environmental reliability of the selected alternative design solutions.